The Animal Research War - Conn, P. author. aut Link
XX, 199 p.
Keywords: This thoughtful and surprising book analyzes the effect of animal extremism on the world's scientists, their institutions, and professional societies. The Animal Research War traces the evolution of the animal rights movement, profiles its leadership, and reveals the truth behind university animal research.